A Qualitative Analysis of Offenders' Emotional Responses to Perpetrating Sexual Assault. (June 2018) - Brennan, Carolyn L.; Swartout, Kevin M.; Cook, Sarah L.; Parrott, Dominic J.
The purpose of this study was to understand sexual assault perpetrators' emotional responses to perpetration to facilitate treatment development and to better understand processes that may give rise to repeat perpetration. Sixty-one firsthand narratives of sexual assault perpetration, posted onReddit.com, were analyzed using qualitative text analysis. The analysis revealed four primary emotional responses to perpetrating sexual assault: shame, guilt, depression, and anger. Each emotional response was associated with different contextual features that appeared in the narratives. Shame co-occurred with perpetrator alcohol use and consent confusion, guilt co-occurred with perpetrators' stated self-growth, anger co-occurred with denial of responsibility and hostility toward women, and depressed affect co-occurred with social isolation following perpetration. The findings indicate certain emotional responses may be more adaptive than others for protecting against repeat perpetration. This research has important implications for the treatment of perpetrators and supports the idea that self-image and perceived social context may be important treatment targets.